HUBUNGAN FAMILY SUPPORT DAN BREASTFEEDING SELF EFFICACY PADA IBU MENYUSUI PMB YULI BAHRIAH - Bahriah, Yuli; Yuni Kurniati (LPPM STIKes Mitra Adiguna, 2024)
Breast milk (ASI) is considered the best and most important food for babies up to 6 months of age without the addition of other foods. The success of breastfeeding is very dependent on the support provided, both from the family and from the mother's self-efficacy in breastfeeding. The mother's condition can also influence breastfeeding success, such as confidence in her breastfeeding ability (breastfeeding self-efficacy). This study aims to determine the relationship between family support and breastfeeding self-efficacy (breastfeeding self-efficacy) with the success of providing exclusive breastfeeding to breastfeeding mothers at PMB Yuli Bahriah. The method used is quantitative by designcross-sectional, and the sample consisted of 20 breastfeeding mothers in the PMB Yuli Bahriah Kertapati work area in 2024. Data collection was carried out using a questionnaire with specific questions regardingfamily support and the success of exclusive breastfeeding.Breastfeeding self-efficacy measured using a scaleBreastfeeding Self-Efficacy (BSE) and analyzed by testchi-square. The research results show that there is a significant relationship betweenfamily support, breastfeeding self-efficacy, and the success of exclusive breastfeeding. Family support plays an important role in the success of exclusive breastfeeding, because it helps babies and families understand the importance of breastfeeding. Mothers also need to increase their self-confidence and motivation to breastfeed as well as knowledge about correct breastfeeding techniques through health service counseling.